(untitled) (Indian Journal of Animal Production and Management, 2013)
Records of 2001 AB (Alpine X Beetal) and SB (Saanen x Beetal) crossbred kids upto six months of age were analyzed to study the effect of birth weight on mortality and morbidity. Irrespective of sex average birth weight was 3.06 kg. Male kids had slightly higher (3.140 ± 0.017 kg) than female (2.964 ± 0.016 kg). The mortality rate for group 1 (<2.6 kg), group 2 (2.6 to 3.1 kg), group 3 (3.2 to 3.7 kg) and group 4 (> 3.7 kg) were 18.20, 14.57, 14.24 and 17.71 %, respectively. In SB male kids, mortality rate was found significantly (P<0.05) higher than other groups. Morbidity rate was recorded to be 35.33% in kids up to the age of six months. Morbidity rate was high in group 1 (36.78%) and in group 4 (36.75%) than group 2 (33.86%) and group 3 (35.75%) but difference was found non-significant. The probable reason for high kid mortality and morbidity among low birth weight groups were low energy reserves and lower thermo-regulatory capacity. Thus, the birth of lighter kids is a serious economic loss and calls for checking the nutrition of the mother in advanced stage of pregnancy. High mortality rate and morbidity rate in birth weight group higher than the average may be attributed to some unknown abnormality in the kid.